2013
DOI: 10.1172/jci66533
|View full text |Cite
|
Sign up to set email alerts
|

LXRβ/estrogen receptor-α signaling in lipid rafts preserves endothelial integrity

Abstract: Liver X receptors (LXR) are stimulated by cholesterol-derived oxysterols and serve as transcription factors to regulate gene expression in response to alterations in cholesterol. In the present study, we investigated the role of LXRs in vascular endothelial cells (ECs) and discovered that LXRβ has nonnuclear function and stimulates EC migration by activating endothelial NOS (eNOS). This process is mediated by estrogen receptor-α (ERα). LXR activation promoted the direct binding of LXRβ to the ligand-binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Therefore, lipid rafts are a necessary component of the immune synapse: cells receive antigen stimulation, the signal is enriched to stimulate parts of the molecular aggregates, and lipid rafts undergo dynamic changes. For example, the inner layer of plasma membrane contains acytelated tyrosine protein kinase family (Ishikawa et al, 2013). Lipid rafts are dispersed in the plasma membrane and can drift sideways.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lipid rafts are a necessary component of the immune synapse: cells receive antigen stimulation, the signal is enriched to stimulate parts of the molecular aggregates, and lipid rafts undergo dynamic changes. For example, the inner layer of plasma membrane contains acytelated tyrosine protein kinase family (Ishikawa et al, 2013). Lipid rafts are dispersed in the plasma membrane and can drift sideways.…”
Section: Discussionmentioning
confidence: 99%
“…Mice used for macrophage isolation were wild-type, era −/− or lxrα −/− ;lxrβ −/− (Ishikawa et al, 2013). Processes in endothelial cells were interrogated in primary bovine aortic endothelial cells (BAEC)(Chambliss et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this extranuclear signalling by LXR required Ser118 phosphorylation of ERα, which facilitated the association of these two receptors, presumably occurring directly at the plasma membrane. Furthermore, this Ser118 phosphorylation of the membrane pool of ER was demonstrated to depend on LXR activation and to be necessary for stimulating the activity of endothelial nitric oxide synthase in response to both ER and LXR ligands 108 . This suggests that, as in the case of the nuclear ERα, in which Ser118 phosphorylation promotes transcriptional activity, this specific phosphorylation also regulates membrane steroid receptor function.…”
Section: Physiological Implicationsmentioning
confidence: 97%
“…Recent studies have shown that in the context of blood vessel repair membrane ERα does not operate alone but colocalizes with liver X receptor-β (LXRβ; also known as NR1H2) 108 (FIG. 4c).…”
Section: Physiological Implicationsmentioning
confidence: 99%